AN ANALYSIS OF INDONESIAN ENGLISH CODE SWITCHING IN ELECTRONIC MAILS - Cecilia Titiek Murniati (Soegijapranata Catholic University, 2004)
This paper attempts to analyze and describe the Indonesian English code switching in electronic mails using Gumperz and Romaines classifications of code switching. The results showed that the Indonesian English code switching tend to take place within sentence boundary rather than between sentence boundary. The findings also reveal that some words or phrases undergo morphological adaptation such as affixation and reduplication. With regard to the function of code switching, the Indonesian English code switching are employed as interjections/sentence fillers, message qualification, personalization, and lexical gap-filling